O Daomé e suas amazonas no século XVIII e XIX: leituras a partir de Frederick Forbes e Richard Burton - Suguiama, Danielle Yumi [UNIFESP] (2019)
This research aims to analyze the visions presented by Frederick E. Forbes and Richard F. Burton about the Kingdom of Dahomey and the “amazons”. The sources used were: Dahomey and the dahomans and A mission to Gelele. Although both are english representatives in the Kingdom of Dahomey, their considerations about the kingdom and the natives differ significantly. The differences in their descriptions originated from the distinct contexts each of them encountered during their travels.